Author Correction: A Myc enhancer cluster regulates normal and leukaemic haematopoietic stem cell hierarchies - Bahr, Carsten; Uslu, Veli Vural; Trumpp, Andreas (Nature, 2018)
In the originally published version of this Letter, ref. 43 was erroneously provided twice. In the ‘Estimation of relative cell-type-specific composition of AML samples’ section in the Methods, the citation to ref. 43 after the GEO dataset GSE24759 is correct. However, in the ‘Mice’ section of the Methods, the citation to ref. 43 after ‘TAMERE’ should have been associated with a new reference1. The original Letter has been corrected online (with the new reference included as ref. 49).
Gesehen am 03.03.2020